Using an educational program based on health belief model to improve the preventive behaviors of nurses against cardiovascular diseases - Shahram Ghasemi Amraei; Farideh Malekshahi; Fateme Goudarzi; Farzad Ebrahimzadeh (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: An unhealthy lifestyle can threaten the health of nursing staff, especially in the context of cardiovascular diseases (CVDs). Considering the importance of health education in promoting preventive behaviors against these diseases, this study aimed to evaluate the effect of an educational program based on the health belief model (HBM) on improving preventive behaviors of nurses against CVDs. MATERIALS AND METHODS: This is a randomized controlled trial with a pretest-posttest design conducted on 104 nursing staff of Imam Khomeini Hospital in Kuhdasht, Lorestan, Iran, in 2017. They were randomly assigned into two groups of HBM (n = 52) and control (n = 52). The HBM group received the educational intervention for 6 weeks, one session per week each for 30-40 min. They were measured before and after the intervention using a demographic form, a researcher-made HBM questionnaire, Baecke Habitual Physical Activity Questionnaire, and the 3-day food intake record all in Persian. The collected data were analyzed in the Statistical Package for the Social Sciences (SPSS) v. 24 software using the Chi-squared test and paired t-test. RESULTS: The educational program could only increase the perceived severity (22.64 ± 2.22), perceived benefits (50.83 ± 5.22), and perceived self-efficacy (42.37 ± 5.93) of nurses in the HBM group compared to the controls (P < 0.05). The nurses' perceived sensitivity was also increased, but it was not significant (P > 0.05). In the HBM group, a significant change was found in the food intake level for energy (t = 4.79, P = 0.000), protein (t = −2.99, P = 0.004), and unsaturated fat (t = −2.94, P = 0.005) after intervention. No significant difference was observed in the total physical activity score after the intervention (P > 0.05). CONCLUSION: An educational program based on the HBM model can be used to increase the severity, benefits, and self-efficacy of the nurses' preventive behaviors against CVDs and modify their dietary regime.